PEMBERIAN KOMBINASI MIKROMINERAL (Cu, Fe, Zn, Co) DAN VITAMIN (A, B1, B12, C) MELALUI DRINKING WATER TERHADAP PERTUMBUHAN PUYUH ( Coturnix-coturnix japonica L) - Sofatin Fitriyani; Koen Praseno; Silvana Tana (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
This aim of this research was to determine the potential of giving micromineral solution (Cu, Fe, Zn, Co) and vitamins (A, B12, B1, C) as drinking water by somatometrik. The method used is a combination gift mikromineral (Cu, Fe, Zn, Co) and vitamins (A, B12, B1, C) with normal doses, twice the normal dose, four times the normal dose, and which is a combination mikromineral and vitamins. The parameters in this research were body weight and somatometrik. This research used Completely Randomized Design (CRD). The data were analyzed with Analysis of variants (ANOVA) with the help of the SAS program, the results of which showed significant, then proceed to further test, using Duncan test. The analysis showed significant difference in body weight gain, femur length, tibia length of tarsus and metatarsus Tarso length, and do not differ significantly in the length of the beak, wing length, feed consumption and water consumption. Giving combination mikromineral (Cu, Fe, Zn, Co) and vitamins (A, B12, B1, C) as a drinking water has the potential to be used as an alternative in the management of quail with respect to maintenance doses given.Key words : vitamins, microminerals, growth, quail (Coturnix coturnix japonica L.)